Globalization and Foreign Direct Investment in the Textile, Garment, and Leather Industry - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2011)
The subject of this paper is analysis and assessment of foreign direct investment (FDI) as made by transnational corporations in the textile, garment, and leather industry on a world economic scale under conditions of globalization. Significant changes are occurring in the sector and industry structure of global FDI. In terms of the three sectors of the economy, a long-term shift of FDI to the service sector at a cost to investments in manufacturing may be seen. Foreign investments are being made in the textile, garment, and leather industry. They are growing in the long term. However, the dynamics of the FDI streams flowing to this industry is one of the lowest in manufacturing. Over the long term (1990-2007), the share of the textile, garment, and leather industry in global FDI stock decreased from 1.5% to 0.6% in 2007. In spite of the labour-intensive character of this industry, in their bulk, the FDI are destined to the highly developed countries.